(3GdYHbGJ GdYfHQjI aj WHbGJ GdLYaQjIs - (3Bd cGTa GdZWGA, eMeO MSjf Hf Ydj Hf GdQVG Hf ehSi Hf LYaQ, J (B1373 (3g`s
(3ChdgG (B:s
(3GdLRA GdKGfj hgh jTJed Ydi GdWHbI GdKGfjI ef gPg GdfHYI GdRGcjI hChdge (B.. (3ehSi Hf LYaQ (B.. (3CLeYJ GdYdeGA Ydi JbOje hdOg ehSi hCfg Chdi HGdCeQ (B...s
(3BNQgG (B:s
.. (3hjbje eG bO RGY ef YeO GdgOGjI NHQ QGaY , hSbi GdMjG LOK GdQVG heVGYI dOi GdeVGLY , Edi gfG JeJ JQLeI LOfG GdCYXe eMeO QVG (B... (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\106s
(3GdPQjYI (B15\1417s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs